Considering the fate of equestrian sports after the Olympics in Paris 2024 - Małgorzata Lubelska-Sazanów (Journal of Animal Law, Ethics and One Health)
The equestrian sports industry constitutes a lucrative branch of business for numerous stakeholders. This article aims to show the reality of animal welfare standards in modern equestrian sports, its pros, cons and the possible fate of these Olympic disciplines in the nearest future. After presenting the legal foundations of equestrian sports, the latest controversies and most important facts connected with the ethics of using horses in equestrian sports, the problem of the position of horses in these sports is presented, trying to place them somewhere between athletes and victims. As the next step, the main negative aspects of equestrian sports are pointed out, combining the social and psychological aspects of sport rivalry and the impact that human emotions – inevitable in any sporting rivalry – may have on the ethics of using horses. The conclusions present my opinion regarding the possible future of equestrianism, including answering the question as to whether it should remain an Olympic discipline.